Comparison of Prevalence of Influenza and COVID-19: A Report From Hormozgan Province-Iran, 2019-2021 - Khadijeh Ahmadi; Masoumeh Mosazadeh; Ladan Mafakher; Parivash Davoodian; Ebrahim Eftekhar; Mehdi Hassaniazad; Hamed Gouklani (Disease and Diagnosis, 2022)
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and influenza viruses produce a wide range of clinical disease severity, which varies from asymptomatic infection to death. The outbreak of coronavirus disease 2019 (COVID-19) in Wuhan, Hubei, China, followed a seasonal influenza pandemic. The prevalence of influenza has changed since the outbreak of COVID-19. In this study, we have compared the prevalence of influenza and COVID-19 since the onset of the pandemic. Clinical symptoms were also assessed among patients. Materials and Methods: The present study was conducted in a single center on 229456 patients with the SARS in Hormozgan province, Iran, during 2019-2021 before and after the COVID-19 pandemic. Clinical features including age, sex, fever, cough, shortness of breath, nausea, dizziness, headache, body aches, and diarrhea were also analyzed. Results: The results indicated that out of a total of 229456 samples of patients, 71142 (31.00%) and 527 (.22%) cases were diagnosed with positive COVID-19 and positive influenza, respectively. Influenza activity decreased in March 2020 and remained low until September 2021, but it increased to near pre-pandemic seasonal levels since October 2021. The outbreak of influenza decreased by starting the restrictions and health protocols. Furthermore, the analysis of patients’ symptoms indicated that the most prevalent symptoms in influenza patients were fever, cough, and body pain, while the symptoms in COVID-19 patients were cough and headache. Conclusion: Social restrictions and adherence to health protocols could significantly reduce the incidence of seasonal influenza even after controlling the COVID-19 pandemic. Influenza and COVID-19 have similar symptoms in patients, so diagnostic tests are necessary for proper diagnosis and management.